Development of functional chicken patties with incorporation of mango peel powder as fat replacer. Issue 6 (24th February 2020) - Chappalwar, Anita M.; Pathak, Vikas; Goswami, Meena; Verma, Arun Kumar
Abstract : Purpose: The purpose of this study is to develop functional chicken patties with incorporation of mango peel powder as a fat replacer. Design/methodology/approach: Low-fat chicken patties were developed by incorporating mango peel powder as fat replacer at 1.0, 2.0 and 3.0% level to replace 50% vegetable oil in the formulation. The product was evaluated for various physico-chemical properties and sensory attributes. Findings: There was a significant difference ( p < 0.05) between control and treatments for all physico-chemical properties except product pH and protein content. The emulsion pH, emulsion stability, water activity, fat and cholesterol content of mango peel treated chicken patties were significantly ( p < 0.01) lower, however, cooking yield, moisture content, fat retention and moisture retention values were significantly ( p < 0.01) higher than control. All mineral content decreased significantly ( p < 0.05) in treatments except potassium and phosphorous content. Incorporation of mango peel powder had a significant ( p < 0.05) effect on textural and colour parameters. Sensory scores decreased significantly ( p < 0.05) in treatments, however, the product was well acceptable up to 2% of mango peel powder incorporation. Originality/value: Fat has an important role in comminuted meat products, its reduction results in rubbery and dry textured products and poses difficulties in terms of flavour and texture. Meat products with high-fat content may exert a great harmful effect on human health such as obesity and high blood cholesterol level. Hence, there is a need for using suitable ingredient, which is able to replace fat without affecting quality. Mango peel may be used as suitable fat replacer at 2% to replace 50% added vegetable fat without affecting quality parameters.